A Phenomenography Study of STEM Teachers’ Conceptions of Using Three-Dimensional Modeling and Printing (3DMP) in Teaching - Anđić, Branko; Ulbrich, Eva; Dana-Picard, Thierry (Noah); Cvjetićanin, Stanko; Petrović, Filip; Lavicza, Zsolt; Maričić, Mirjana (Journal of science education and technology, 2023)
There is a large amount of research that indicates that the use of 3DMP in STEM education improves students’ knowledge, motivation, and participation in the learning process. Nevertheless, despite the existing attempts to market 3DMP in education, its adoption in schools remains low. A number of studies with teachers in secondary schools and colleges indicate that teachers’ perceptions of 3DMP are one of the key factors for its successful use. However, to our best knowledge, there is no research that examined STEM upper primary school teachers’ perception on 3DMP. Through phenomenographic approach, this study is seeking to address the existing gaps. Four conceptions of 3DMP teaching emerged: (1) 3DMP as tools for classroom modernization; (2) 3DMP technical and software characteristics’ impact on implementation; (3) 3DMP as a tool for learning and improvement in teaching; (4) 3DMP and students’ professional orientation, teachers’ professional development. These four categories are connected by five key aspects of variation: impact on students, impact on teachers, classroom activity management, authenticity, subject-curriculum matters. The results of our study indicate that the mathematics and science teachers have a more sophisticated opinion on 3DMP than teachers of technical education, engineering, and informatics who mostly require additional training when it comes to using 3DMP in STEM education. Comparatively, science and mathematics teachers need support with implementation of software and 3D printers as a technical tool. Considering that this study’s teachers were early adopters of 3DMP, any future research should explore conceptions of experienced users.